2008
DOI: 10.1103/physrevb.78.125416
|View full text |Cite
|
Sign up to set email alerts
|

Electron-capture decay rate ofB7e@C60by first-principles calculations based on density functional theory

Abstract: Carrying out a first-principles calculation assuming linear relationship between the electron density at Be nucleus and the electron-capture ͑EC͒ decay rate, we explained why 7 Be@C 60 shows higher EC decay rate than 7 Be crystal, which was originally found experimentally by Ohtsuki et al. ͓Phys. Rev. Lett. 93, 112501 ͑2004͔͒. From the results of the calculation, we found that there are inequivalent four stable ͑i.e., lower energy͒ Be sites inside C 60 and that center of C 60 ͑C_C 60 ͒ is the most favorable si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
10
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 28 publications
(31 reference statements)
6
10
0
Order By: Relevance
“…at the Be nucleus. the DFT calculations[5,6]. However, our value is in excellent agreement with the experimental data of Kraushaar et al[16] of the direct measurement of the 7 Be half-life in the metal source T…”
supporting
confidence: 90%
See 2 more Smart Citations
“…at the Be nucleus. the DFT calculations[5,6]. However, our value is in excellent agreement with the experimental data of Kraushaar et al[16] of the direct measurement of the 7 Be half-life in the metal source T…”
supporting
confidence: 90%
“…The corresponding relative decrease of the electron density in our calculations is 0.28%, in qualitative accord with the value of 0.17% in Refs. [5,6]. The reason for the enhanced electron density in Be@C 60 might be a slight hybridization of Be's and C 60 's orbitals, as suggested in Ref.…”
Section: Examination Within the Framework Of Hartree-fock Based Mmentioning
confidence: 75%
See 1 more Smart Citation
“…This implied that the 7 Be atoms are located in a unique environment inside C 60 . This large change in the half-life is firmly caused by the electron dens-ity at the nucleus position and the magnitude of the change has also been explained theoretically [18].…”
Section: Introductionmentioning
confidence: 61%
“…The authors interpreted the observations by calculating the electron density at the position of 7 Be inside C 60 . Based on these experiments, Morisato et al used density functional theory to calculate and explain why 7 Be@C 60 shows higher EC decay rate than 7 Be metal found in the above experiments in detail, and found that there are inequivalent four stable Be sites inside C 60 and that center of C 60 is the most favorable site [59]. Recently, a similar analysis was published in 2012 [60].…”
Section: The Purcell Effect and The Neutron: Qualitative Featuresmentioning
confidence: 87%